2011
DOI: 10.1128/aem.02337-10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Concentration and Molecular Enrichment Approach for Sensitive Detection of Escherichia coli and Shigella Species in Potable Water Samples

Abstract: In this work, we used a rapid, simple, and efficient concentration-and-recovery procedure combined with a DNA enrichment method (dubbed CRENAME [concentration and recovery of microbial particles, extraction of nucleic acids, and molecular enrichment]), that we coupled to an Escherichia coli/Shigella-specific real-time PCR (rtPCR) assay targeting the tuf gene, to sensitively detect E. coli/Shigella in water. This integrated method was compared to U.S. Environmental Protection Agency (EPA) culture-based Method 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 28 publications
1
49
1
Order By: Relevance
“…The uidA gene (coding for ␤-D-glucuronidase) was chosen as the most frequently used target gene for E. coli (24,38,39,40,41). Its specificity, however, has been questioned (27), and therefore, two other promising gene targets, tuf (coding for a protein elongation factor) (25), present in one to two copies, and rodA (coding for a unspecified protein, affecting cell shape and amdinocillin) (26), were also selected. rodA was included as a single-copy gene target and therefore had the potential to act as a molecular proxy for an E. coli cell count.…”
Section: Test Panel Specificity and (Rt-)q-pcr Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The uidA gene (coding for ␤-D-glucuronidase) was chosen as the most frequently used target gene for E. coli (24,38,39,40,41). Its specificity, however, has been questioned (27), and therefore, two other promising gene targets, tuf (coding for a protein elongation factor) (25), present in one to two copies, and rodA (coding for a unspecified protein, affecting cell shape and amdinocillin) (26), were also selected. rodA was included as a single-copy gene target and therefore had the potential to act as a molecular proxy for an E. coli cell count.…”
Section: Test Panel Specificity and (Rt-)q-pcr Assaysmentioning
confidence: 99%
“…In order to select a Q-PCR assay and subsequently design RT-Q-PCR assays for E. coli with the highest levels of specificity, sensitivity, and efficiency, a literature review identified three frequently used functional genes for E. coli, uidA (24), tuf (25), and rodA (26) for comparison. The uidA gene (coding for ␤-D-glucuronidase) was chosen as the most frequently used target gene for E. coli (24,38,39,40,41).…”
Section: Test Panel Specificity and (Rt-)q-pcr Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Quality control for each batch of mCP agar was performed, and filter, buffer, and rinse water blanks were included as sterility controls. For performing CRENAME on concentrated water samples, GN-6 filters were aseptically transferred to 3 individual 15-ml polypropylene tubes (Sarstedt, Newton, NC, USA) and processed as described by Maheux et al (27,28).…”
Section: Determination Of the Analytical Limit Of Detection (Lod) Of mentioning
confidence: 99%
“…Colonies presenting discordant results between the phenotype on mCP agar and cpa rtPCR were identified by sequencing the 16S rRNA and cpa genes. Finally, we compared mCP agar and a CRENAME (concentration and recovery of microbial particles, extraction of nucleic acids, and molecular enrichment) procedure plus cpa rtPCR (CRENAME ϩ cpa rtPCR) for their abilities to detect C. perfringens spores in drinking water (27,28).…”
mentioning
confidence: 99%